Dynamics of Social Stratification in the Bugis Bone Community - Yanis, Muhammad; Rusdi, Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research is descriptive analytics are trying to find and describe about the social stratification in society Bugis Bone, Sulawesi Selatan. The type of data used in this research is primary data and secondary data. Primary data obtained from the informants or people who live in the study site. Research data include things related with social stratification applicable in the society Bugis Bone. The results of the study to find a conclusion that a system of stratification Bugis society still tend to askriptif based on the lineage of nobility.